An in vivo study of the pharmacological activities of a methanolic acetate fraction of Pistia stratiotes L.: An ethno‐medicinal plant used in Bangladesh. Issue 3 (24th October 2018) - Hussain, Md. Saddam; Ibrahim, Md.; Hasan, Md. Murad; Aziz, Mohammad Tarek; Suchi, Suzia Akter; Uddin, Md. Giash
Abstract: Background: The present study covered an assessment of methanolic acetate fractions of Pistia stratiotes, commonly known as water lettuce, for analgesic, anti‐inflammatory, and CNS depressant activities. Methods: The methanol acetate fractions were extracted from Pistia stratiotes and administered to the experimental animals as 200 and 400 mg/kg doses to determine the effect on acetic acid‐induced writhing and formalin‐induced licking and biting, for the assessment of analgesic activity. The anti‐inflammatory assay was done using the carrageenan‐induced hind paw edema method, while assessment of CNS depressant activity was done using the open field and hole cross tests. The effects were compared to standard reference drugs. Results: At both doses (200 and 400 mg/kg body weight), the methanolic acetate extract of P. stratiotes showed significant analgesic action ( P  <   0.05) against acetic acid‐induced writhing. The extract was also found to give significant protection against licking and biting at both doses. The methanolic acetate extract of P. stratiotes showed a significant ( P  <   0.05) anti‐inflammatory effect from 0 minutes up to 3 hours in the carrageenan‐induced paw edema test. In the CNS depressant assay, the methanolic acetate extract showed significant ( P  <   0.05) depressant activity at both doses from 30 to 120 minutes in both the hole cross and open field tests. Conclusion: Thus we can conclude that P. stratiotes extracts have significant analgesic, anti‐inflammatory, and CNS depressant activity, compared to standard compounds, in an animal model.